The Therapeutic Potential of Anticoagulation in Organ Fibrosis - Oh, Hanna; Park, Hye Eun; Song, Min Su; Kim, HaYoung; Baek, Jea-Hyun (Frontiers in Medicine, 2022)
Fibrosis, also known as organ scarring, describes a pathological stiffening of organs or tissues caused by increased synthesis of extracellular matrix (ECM) components. In the past decades, mounting evidence has accumulated showing that the coagulation cascade is directly associated with fibrotic development. Recent findings suggest that, under inflammatory conditions, various cell types (e.g., immune cells) participate in the coagulation process causing pathological outcomes, including fibrosis. These findings highlighted the potential of anticoagulation therapy as a strategy in organ fibrosis. Indeed, preclinical and clinical studies demonstrated that the inhibition of blood coagulation is a potential intervention for the treatment of fibrosis across all major organs (e.g., lung, liver, heart, and kidney). In this review, we aim to summarize our current knowledge on the impact of components of coagulation cascade on fibrosis of various organs and provide an update on the current development of anticoagulation therapy for fibrosis.